'Dematerialization' in times of economic crisis: A regional analysis of the Spanish economy in material and monetary terms. (September 2022) - Schaffartzik, Anke; Duro, Juan Antonio
Highlights: An unprecedented drop in material consumption accompanied the 2007 crisis in Spain. Construction activities were key in both the expansive and the contractive period. Unsustainable material growth coincided with decreasing subnational inequality. 'Dematerialization' was associated with increased inequality. A just socio-ecological transformation requires dematerialization by design.